Penerapan Manajemen Kinerja pada Usaha Mikro Kecil Menengah di Tanjungpinang - Wahyuni, Riska Dwi; Putri, Lai Sen Mih Mustika; Maulana, Irfan; Satriadi, Satriadi (Sahabat Publikasi, 2024)
This study examines the application of performance management in Micro, Small and Medium Enterprises (MSMEs) in Tanjungpinang at KATENG Backyard Coffee. MSMEs have a strategic role in local economic growth, so they still need efforts to improve the implementation of performance management. Therefore, this study aims to analyze the application of performance management in KATENG Backyard Coffee. The research method to be used is descriptive qualitative, using data collection techniques through direct interviews with owners, employees of KATENG Backyard Coffee. The results of the research obtained that in implementing performance management carried out by Kateng Backyard Coffee has provided good results with a flexible approach that provides good results, stability in the team, providing training and development to employees, the existence of SOPs as a benchmark in work, and continuing to innovate in the future.